Book loan policy awareness and borrowing patterns of undergraduate students of the University of the Philippines, Diliman - Gabo, Christian Clark Ian B. (2009)
Library policies exist to increase the efficiency and effectiveness of the library services. Library policies focusing specifically on books loans aims to increase the efficiency and effectiveness of circulation of books. Since policies are ineffectual if a majority of the people concerned are not aware of them, this study aim to determine the effective methods of increasing book loan policy awareness among the students, in order to someday formulate methods in properly increasing awareness and compliance to the said policies.